(untitled) (Sociologisk Forskning, 2003)
Vertreter and Stellvertreter: On acting from a position The article is part of an attempt to build a structural theory of interaction. It tries to identify a limited set of acting positions - Vertreter, Stellvertreter and personal acting. The theoretical point concerning these acting positions is that each demand a stable set of acts, and work from different logics. This stability is unmoved by such things as changes in the identity or in the preferences of the actor. The actor must subordinate himself under the logic of the position if he is to be able to co-operate with other actors. The Stellvertreter acts in another’s name, alieno nomine agere, while the Vertreter answers for another’s acts. In many situations, an actor may act as the one or the other - the priest acts in the name of God and answers for the acts of the church, which is problematic since the two may be opposed, even antagonistic, to each other.